Transcriptomic and molecular genetic analysis of the cell wall salvage response of Aspergillus niger to the absence of galactofuranose synthesis - Park, Joohae (Cell Microbiol, 2016)
The biosynthesis of cell surface‐located galactofuranose (Galf)‐containing glycostructures such as galactomannan, N‐glycans and O‐glycans in filamentous fungi is important to secure the integrity of the cell wall. UgmA encodes an UDP‐galactopyranose mutase, which is essential for the formation of Galf. Consequently, the ΔugmA mutant lacks Galf‐containing molecules. Our previous work in Aspergillus niger work suggested that loss of function of ugmA results in activation of the cell wall integrity (CWI) pathway which is characterized by increased expression of the agsA gene, encoding an α‐glucan synthase. In this study, the transcriptional response of the ΔugmA mutant was further linked to the CWI pathway by showing the induced and constitutive phosphorylation of the CWI‐MAP kinase in the ΔugmA mutant. To identify genes involved in cell wall remodelling in response to the absence of galactofuranose biosynthesis, a genome‐wide expression analysis was performed using RNAseq. Over 400 genes were higher expressed in the ΔugmA mutant compared to the wild‐type. These include genes that encode enzymes involved in chitin (gfaB, gnsA, chsA) and α‐glucan synthesis (agsA), and in β‐glucan remodelling (bgxA, gelF and dfgC), and also include several glycosylphosphatidylinositol (GPI)‐anchored cell wall protein‐encoding genes. In silico analysis of the 1‐kb promoter regions of the up‐regulated genes in the ΔugmA mutant indicated overrepresentation of genes with RlmA, MsnA, PacC and SteA‐binding sites. The importance of these transcription factors for survival of the ΔugmA mutant was analysed by constructing the respective double mutants. The ΔugmA/ΔrlmA and ΔugmA/ΔmsnA double mutants showed strong synthetic growth defects, indicating the importance of these transcription factors to maintain cell wall integrity in the absence of Galf biosynthesis.